2001
DOI: 10.1037/0022-0663.93.2.330
|View full text |Cite
|
Sign up to set email alerts
|

How many do you see? The use of nonspoken representations in first-grade mathematics lessons.

Abstract: Not all relevant instructional information comes in the form of spoken words. In the present study, the authors examine multiple modalities of nonspoken forms of representation-specifically gestures, pictures, objects, and writing-used by 3 teachers in 3 years of lst-grade math lessons. Teachers frequently used visually based modalities of representation and tended to produce combinations of representational forms rather than isolated representations. There were individual differences in their preference for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 24 publications
1
60
0
4
Order By: Relevance
“…Sowell 1989) simply using diagrammatic representations in the teaching of mathematics does not necessarily impact on the learning of pupils. This consideration of how diagrammatic representations can be used is in agreement with the issues around the use of various representations highlighted in the review of the literature (BoultonLewis 1998;Cobb, Yackel and Wood 1992;Flevares and Perry 2001;Hall 1998). In terms of teacher knowledge, this progression also emphasises how teacher knowledge can be more integrated; taking Ball, Thames and Phelps' (2008) model for pedagogical content knowledge as an example, the possible connections between knowledge of content and teaching (KCT) in terms of the representations that can be used to explain a concept and knowledge of content and students (KCS) in terms of the potential difficulties faced by students is evident.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Sowell 1989) simply using diagrammatic representations in the teaching of mathematics does not necessarily impact on the learning of pupils. This consideration of how diagrammatic representations can be used is in agreement with the issues around the use of various representations highlighted in the review of the literature (BoultonLewis 1998;Cobb, Yackel and Wood 1992;Flevares and Perry 2001;Hall 1998). In terms of teacher knowledge, this progression also emphasises how teacher knowledge can be more integrated; taking Ball, Thames and Phelps' (2008) model for pedagogical content knowledge as an example, the possible connections between knowledge of content and teaching (KCT) in terms of the representations that can be used to explain a concept and knowledge of content and students (KCS) in terms of the potential difficulties faced by students is evident.…”
Section: Discussionmentioning
confidence: 69%
“…In particular, teachers cannot assume that students recognise representations in the manner expected (Hall 1998); the meaning that particular representations have for the teacher may be quite different from the meaning they have for the student (Cobb, Yackel and Wood 1992). Therefore, if particular representations are to be used in the classroom, then teachers need to support students in learning to interpret representations (Flevares and Perry 2001), through providing "effective transitional experiences" (Boulton-Lewis 1998, 222) to support students' progression onto using these different representations.…”
Section: The Use Of Diagrammatic Representations In the Teaching Of Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Valenzeno, Alibali, and Klatzky's (2003) research indicated that this latter type of gesture can be especially vital to students' understandings of mathematical concepts by linking verbal speech to visible objects (cf. Flevares & Perry, 2001). In synthesizing the findings across several studies on gestures in mathematics, Sfard (2009) concluded that "gestures are crucial to the effectiveness of mathematical communication .…”
Section: Discipline-specific Uses Of Gesturesmentioning
confidence: 99%
“…Broad studies have been conducted regarding how instructor gestures influence the learning process. Math and science teachers frequently use their hands to depict information [2], [3], [4], [5]. Gesture in instruction has been shown to increase learning of a wide variety of mathematical concepts, including mathematical equivalence [6], [7], [8].…”
Section: Prior Workmentioning
confidence: 99%